PENGARUH IMPLEMENTASI TOTAL QUALITY MANAGEMENT (TQM) TERHADAP KEPUASAN KERJA KARYAWAN (STUDI KASUS PADA RUMAH SAKIT IBU DAN ANAK (RSIA) ZAINAB PEKANBARU) - Putri Widiyanti Dinda; Samsir Samsir; Daulay N Iwan (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2022)
This study was conducted at the Zainab Mother and Child Hospital (RSIA)Pekanbaru and the purpose of this study was to find out how teamwork influencesemployee job satisfaction, to find out how employee job satisfaction, to find outhow involvement and empowerment influence employees and to find out whichTotal Quality Management (TQM) variable is the most dominant in the jobsatisfaction of the Zainab Pekanbaru Mother and Child Hospital (RSIA)employees. The population is the Zainab Pekanbaru Mother and Child Hospital(RSIA) employees, totaling 250 people using the slovin formula which makes asample of 154 employees. This study was analyzed using multiple linearregression analysis. From the results of the study it can be concluded that there isa significant influence between teamwork on job satisfaction and betweencontinuous improvement on job satisfaction because the value of tcount is greaterthan ttable. Furthermore, the involvement and empowerment of employees affectjob satisfaction, because the value of tcount is greater than ttable. Simultaneouslythere is a significant influence between teamwork, continuous improvement,employee involvement and empowerment on job satisfaction at the Zainab Motherand Child Hospital (RSIA) Pekanbaru because the fcount value is greater than theftable. It is known that all independent variables, namely teamwork, continuousimprovement, the involvement of employees jointly contribute to employee jobsatisfaction at Zainab Pekanbaru Mother and Child Hospital (RSIA) of 40.90%.This means that teamwork, continuous improvement, involvement andempowerment of employees affect job satisfaction. The rest is influenced by otherfactors not examined in this study. Keywords: Teamwork, Continuous Improvement, Employee Engagement andEmpowerment And Employee Job Satisfaction